Aluminium Oxide (AL2O3) Nanoparticles with Long Life Coolant for Car Radiator Application - Aravinda, Kottasamy; K., Kadirgama; D., Ramasamy; Mahendran, Samykano; M. M., Noor; M. M., Rahman (2016)
This paper discusses about Aluminium Oxide (Al₂O₃) nanoparticles with long life coolant for car radiator application. The research is conducted in order to prove that addition of Al₂O₃ nanoparticles with varying concentration and flow rate provides a better heat transfer efficiency compared to usage of distilled water with as radiator coolant. The objective of the research is to improve and create a new radiator coolant based on collaboration of Al2O3 nanoparticles with readily available long life coolant. The nanoparticle used in the research is Al₂O₃ nanoparticles between ranges of size 40-80 nm. The tested concentration of Al₂O₃ nanofluids are as of 0.01%, 0.03%, 0.05%, 0.07% and 0.09%. The nanofluids are heated at heating range of five and eight minutes. The tested flow rate are of 1.60×10-4m3/s and 9.76x10-5m3/s. Varying flow rate and volume concentration of Aluminium Oxide (Al₂O₃) nanoparticles fused together with long life coolant for car radiator application shows better thermal absorbing efficiency than current radiator heat transfer fluid.